HIV and the menopause: A review. Issue 1 (March 2018) - Bull, Lauren; Tittle, Victoria; Rashid, Taslima; Nwokolo, Nneka
Effective antiretroviral therapy has resulted in a close to normal life expectancy for people living with HIV. This has led to a shift in the age distribution of women living with HIV in the UK, with one in three attending for HIV care estimated to be aged 45–56 years in 2014. The lack of experience of many HIV physicians in managing menopause, and the perceived complexity of managing menopause in women living with HIV by general practitioners means that many women are unable to access appropriate care and support. This is aggravated by the relative paucity of data on menopause in women living with HIV and conflicting results in this field, for example with regard to age of onset of menopause and symptomatology experienced. Furthermore, women living with HIV have unique considerations such as potential interactions between antiretroviral therapy and menopause hormone therapy (previously called hormone replacement therapy) and other physiological concerns such as a multifactorial propensity towards decreased bone mineral density and potentially increased cardiovascular risk. On the whole, menopause hormone therapy is probably underutilised in this group of women due to perceived concerns around drug–drug interactions, as well as fears shared with women in the general population about menopause hormone therapy. Menopausal women should be given adequate information on symptomatology, lifestyle modification and treatment options including menopause hormone therapy. Furthermore, a holistic approach which considers the increased burden of poor mental health in this population is essential.